Role of a Pdlim5:PalmD complex in directing dendrite morphology - Srivastava, Yogesh; Donta, Maxsam; Mireles, Lydia L.; Paulucci-Holthauzen, Adriana; Waxham, M. Neal; McCrea, Pierre D. (Frontiers in Cellular Neuroscience, 2024)
Neuronal connectivity is regulated during normal brain development with the arrangement of spines and synapses being dependent on the morphology of dendrites. Further, in multiple neurodevelopmental and aging disorders, disruptions of dendrite formation or shaping is associated with atypical neuronal connectivity. We showed previously that Pdlim5 binds delta-catenin and promotes dendrite branching (Baumert et al., J Cell Biol 2020). We report here that Pdlim5 interacts with PalmD, a protein previously suggested by others to interact with the cytoskeleton (e.g., via adducin/ spectrin) and to regulate membrane shaping. Functionally, the knockdown of PalmD or Pdlim5 in rat primary hippocampal neurons dramatically reduces branching and conversely, PalmD exogenous expression promotes dendrite branching as does Pdlim5. Further, we show that each proteins' effects are dependent on the presence of the other. In summary, using primary rat hippocampal neurons we reveal the contributions of a novel Pdlim5:PalmD protein complex, composed of functionally inter-dependent components responsible for shaping neuronal dendrites.